BEHAVIOR OF THE COACH IN LEADER’S ROLE - Enes Huseinagić; Adnan Hodžić (Sport Scientific And Practical Aspects, 2025)
This work wanted to research in what way is behavior of participants in a role of coaching the sport teams determined between different influences of his personality characteristics. Concerning the area of leading is a very complex problem, domains of research are pointed onto theoretical and research problem of leading as fundamental (basic) sport management functions. Research is conducted trough Fiedler’s contingency leading model. Fiedler’s contingency model describes how situation changes relations between efficient leading and results and measuring the facts called less preferred converrker. The accent of research is pointed onto the level and direction of group and personality structure influence on leading style of sort coaches. Research results are determined by LPC leading style and are articulated trough domains of personality by being introvert, Good Samaritan and innersole oriented.